PEMBUATAN SERBUK INSTAN KUNYIT PUTIH (Curcuma zedoaria (Bergius) Roscoe.) DAN KACANG MERAH (Phaseolus vulgaris L.) SEBAGAI ANTIOKSIDAN - Sabilah, Salma; Andriani, Susi; Suharti, Suharti (Sekolah Tinggi Ilmu Kesehatan Holistik, 2020)
Background: Free radicals can trigger the causes of such diseases as cancer,kidney disorders, heart attacks and cataracts. Antioxidants can help neutralize free radicals in the human body. Instant powder white tumeric and red beans are rich in antioxidant deposits because white tumeric and red beans contain the polyphenol known as antioxidants. Objective: The aim of this study is to make available existing instant powder white tumeric (Curcuma zedoaria) and red beans (Phaseolus vulgaris L.) as antioxidants and search for the best formulation based on organoleptic test in three weeks. Method: This design of this study is action research, which consists of stages planning, implementation, observation and reflection or evaluation. The study is divided into the first two stages, the process by which sedimentation is produced criztallization methods and phase two, availability of pollen organoleptic test instan powder. Results: The results of study of the production of white tumeric and red beans instant powder have produced varying quantities of FI 164 grams, FII 361 grams and FIII 541 grams. The results of all three samples organoleptic test showed no significant changes in smell, shape, taste and color. The best formula after three weeks of organoleptic test is FII 1:1 (essence 400 ml : sugar 400 g). Conclusion: : The study shows that white tumeric and red beans instant powder that have the best formulation based on three weeks of organoleptic testing on FII 1:1 (essence 400 ml : sugar 400 g).